RoadRAT – A new framework to assess the probability of inundation, wave runup, and erosion impacting coastal roads - Hallin, Caroline; Adell, Anna ; 0000-0003-3207-7718; Almström, Björn; Kroon, Aart; Larson, Magnus (Coastal Engineering, 2025)
This paper introduces a new framework – RoadRAT - to calculate the probability of inundation, wave runup, and storm erosion impacting coastal roads. Extreme value analysis is applied to annual maxima of observed and simulated still water level levels (SWL), total water levels (SWL + runup), and storm erosion volumes. The probability of impact on the road is derived both for the present conditions and for future conditions considering long-term evolution of the coastline in response to sea level rise and projected continuation of historical trends. RoadRAT is intended for screening at a regional scale (>100 km) to identify vulnerable road segments that need further attention. A case study was conducted on the south coast of Sweden to demonstrate the framework. The results indicate that the main coastal road has a low probability of impact under present conditions, but that it will increase in the future under changing climatic conditions. In 2150, which is the target year for the analysis, several kilometres of the road will be lost to erosion, and flooding and runup will frequently impact parts of the remaining road. In future applications, RoadRAT could be coupled with models that describe the consequences of inundation, wave runup, and storm erosion for road serviceability and transport.
Publisher Copyright: © 2025 The Authors
Keywords: Extreme value analysis; Inundation; Road infrastructure; Runup; Sea level rise; Storm erosion